Executive Functions of Divers Are Selectively Impaired at 20-Meter Water Depth - Steinberg, Fabian; Doppelmayr, Michael (Frontiers in Psychology, 2017)
Moving and acting underwater within recreational or occupational activities requires intact executive functions, since they subserve higher cognitive functions such as successful self-regulation, coping with novel situations, and decision making; all of which could be influenced by nitrogen narcosis due to elevated partial pressure under water. However, specific executive functions that could provide a differentiated view on humans’ cognitive performance ability have not yet been systematically analyzed in full-water immersion, which is a research gap addressed within this approach to contribute to a better understanding of nitrogen narcosis. In this study, 20 young, healthy, and certified recreational divers participated and performed three different executive-function tests: the Stroop test (Inhibition), the Number-letter test (Task switching),the 2-back test (Updating/Working memory), and a simple reaction time test (psychomotor performance). These tests were performed once on land, at 5-meter water depth, and at 20-meter water depth of an indoor diving facility in standardized test conditions (26°C in all water depths). A water-proofed and fully operational tablet computer was used to present visual stimuli and to register reaction times. Performance of the simple reaction time test was not different between underwater and land testing, suggesting that reaction times were not biased by the utilization of the tablet in water immersion.. Executive functions were not affected by the shallow water immersion of 5-meter water depth. However, performance scores in 20-meter water depth revealed a decreased performance in the incongruent test condition (i.e., an index of inhibitory control ability) of the Stroop test, while all other tests were unaffected. Even though only one out of the three tested cognitive domains was affected, the impairment of inhibitory control ability even in relatively shallow water of 20-Meters is a critical component that should be considered for diver’s safety, since inhibition is required in self-control requiring situations where impulsive and automatic behavior must be inhibited. Our interpretation of these selective impairments is based on a discussion suggesting that different neural networks within the central nervous system, which process specific executive functions, are affected differently by nitrogen narcosis.